The Impact of Monetary Policy on Financial Market in South Africa: A VAR Analysis - Noumbissie, Flavien Fokou (Journal of Economics and Behavioral Studies, 2014)
Like in many other countries, the South African financial market facilitates the process of raising capital by channelling funds to more productive economic activity, thereby building the nation’s economy while enhancing job opportunities and wealth creation. The aim of this paper is to assess the impact of monetary policy on financial market in South Africa. It is important to constantly look into this interaction since policy decisions have a direct influence on financial market. A negative response from the market side may jeopardise economic stability. The study uses the vector autoregressive (VAR) model to evaluate the impact of monetary policy on financial market in South Africa. The model consists of five policy instruments as variables; namely: money supply (M3), real exchange rate(ER), discount Rate (R), consumer price index (CPI), gross domestic product (GDP) and the two market related variables: Stock market turnover (S) and Bond market turnover (B). Data is obtained from SARB and OECD databases for a period of 53 quarters from 2000:Q1 to 2013:Q1. By the use of impulse response function (IRF), the study found that given current economic situation in South Africa, stock market turnover reacts positively to money supply; discount rate; real exchange and GDP shocks. On the other hand stock market turnover reacts negatively to CPI economic shocks. To correct CPI negative impact on markets, we suggest that the policymakers could envisage a contractionary monetary policy translated by a proportional cut in money supply through the sales of government securities.